AFFIXATION IN JAVANESE LANGUAGE UTTERED BY PURWOBAKTI VILLAGERS - Magria, Vera; Sari, Yunita (TELL - US JOURNAL, 2020)
This research identifies the kinds of affixes, the process and the function of affixation in Javanese Language uttered by Purwobakti villagers. This research used descriptive qualitative method.Data were gained through participating technique, recording technique, and writing technique. The results of this research show that there are five kinds of prefixes include {ng-}, {di-}, {ben-}, {ke-}, and {ny-}. The five kinds of suffixes include {-e}, {-ne}, {-an}, {-ane}, and {-en}, and infix that is {-cici-}. The process of affixes in this research includes derivational and inflectional affixation. The affixes have function of forming noun, verb, adjective, adverb, and numeric.